Tailoring the preparation of palm oil based alkyd/epoxy resin composite through copper oxide nanoparticle - Ong, Huei Ruey (2016)
Intensive research on the development of polymers from renewable resources has been triggered due to the environmental concerns. Alkyd resin is a green polymer derived from vegetable oil with low cost and higher biodegradability mainly used for organic coating, paint or varnish. On the other hand, epoxy resin is considered as highly reactive polymer may form structural materials for indoor and outdoor applications while blended with fillers in the form of nanocomposites. The alkyd/epoxy blend can overcome the drawbacks of the individual polymers and resulted in improved mechanical properties. Conventional nanocomposites usually require 1-5 wt% filler; most commonly clay, carbon materials or metal/oxide nanoparticles. The present work is an attempt to produce alkyd/epoxy blend containing CuO nanoparticles with its homogeneous distribution to achieve higher mechanical and antimicrobial properties. In the present work palm oil and glycerol were used as starting material to produce alkyd resin. Colloidal CuO nanoparticle was prepared in glycerol and subsequently used alcoholysis–polyesterification process to produce alkyd resin. The nanoparticle formation was monitored by X–ray absorption near edge structure spectroscopy (XANES) and its particle size was confirmed by TEM in the range of ~5 nm. The formation of the alkyd resin was confirmed by FTIR, Raman, 1H–NMR and 13C–NMR analyses and its molecular weight were determined by gel permeation chromatograph (GPC). The antimicrobial activity of the resin was determined via Kirby–Bauer Method and the CuO stability was determined by XANES. The addition of CuO nano-sol to the conventional homogeneous base catalyzed system explored a new catalytic route for the preparation of vegetable oil based alkyd resin that reduced the reaction time from 120 min to 60 min as well as added the antimicrobial properties to the resin. Moreover, alkyd was blended with epoxy resin in order to prepare composite of desired properties and the effect of weight ratio of alkyd/epoxy blend was investigated. The formation of blend and its chemical and mechanical properties were elucidated by standard methods (ASTM). It was found that, the presence of CuO nanoparticle enhanced the mechanical properties of the blend. The CuO incorporated alkyd/epoxy blend at ratio of 30:70 was found to be optimum and its tensile (47 MPa), flexural (138 MPa) and impact strengths (101 J/m2) were higher than the blend without CuO nanoparticle. Moreover, standard micromechanical models (rule of mixture, inverse rule of mixture, takayanagi and halpin-tsai model) and finite element modeling were used to predict the data. The effect of alkyd to epoxy ratio, alkyd polymerization time and CuO nanoparticle modification concerning the tensile, flexural and impact strength was optimized by using response surface methodology (RSM). The composite comprising of alkyd, epoxy and CuO nanoparticle exhibited better mechanical properties, thermal stability and biodegradable, can be considered for both indoor-outdoor applications.